2022
DOI: 10.1101/2022.12.13.22282654
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effectiveness of one dose of MVA-BN smallpox vaccine against monkeypox in England using the case-coverage method

Abstract: Background Like many other countries worldwide, the UK experienced a national outbreak of monkeypox disease in May 2022, with case numbers rising rapidly, mainly among gay, bisexual and other men who have sex with men (GBMSM). To control the outbreak, Modified Vaccinia Ankara-Bavaria Nordic (MVA-BN), an attenuated smallpox vaccine, was offered to high-risk GBMSM. We assessed the effectiveness of a single MVA-BN dose against monkeypox disease in high-risk GBMSM. Methods Monkeypox cases in England were sent ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Nevertheless, a lack of robust antibody responses after one dose of IMVANEX in previously unvaccinated individuals (aged <50) does not suggest a lack of protection, as recent studies have shown that vaccine efficacy against disease after one dose of IMVANEX has been suggested to be as high as 78% when comparing vaccinated with unvaccinated individuals 45 .…”
Section: Monkeypox-convalescent Individualsmentioning
confidence: 99%
“…Nevertheless, a lack of robust antibody responses after one dose of IMVANEX in previously unvaccinated individuals (aged <50) does not suggest a lack of protection, as recent studies have shown that vaccine efficacy against disease after one dose of IMVANEX has been suggested to be as high as 78% when comparing vaccinated with unvaccinated individuals 45 .…”
Section: Monkeypox-convalescent Individualsmentioning
confidence: 99%
“…3 Studies from this recent outbreak reported 9–18% vaccinated participants. 4,5 Smallpox Vaccinia virus-based (VACV) vaccines induce cross-protection against symptoms caused by other orthopoxviruses, including Mpox, 610 but vaccination at childhood does not necessarily provide robust neither permanent immunity against Mpox 11 as is suggested in our patient. Specific memory CD4 + and CD8 + T cells, B cells and antibodies were found to persist >50 years following VACV vaccine.…”
Section: Discussionmentioning
confidence: 69%
“…Two studies based on aggregated data conducted in the United States [16,17] in males 18-49 years old at risk of mpox, found a risk of MPXV infection more than 7 times higher in the unvaccinated compared to the vaccinated, which would be equivalent to an 86% protection conferred by the vaccine. One study in the United Kingdom [15] using the screening method [29] found a vaccine effectiveness of 78% starting 14 days after a single dose. Two studies in the United States, using case-control designs, have provided discordant estimates of VE with one dose of 75% [19] or 36% [18](72% and 41% in immunocompetent individuals, respectively), likely due to differences in the selection criteria for both cases and controls.…”
Section: Discussionmentioning
confidence: 99%
“…Before the current outbreak, no estimates of clinical efficacy were available outside of animal models [13,14]. During the outbreak, estimates of vaccine effectiveness (VE), when administered pre-exposure, have been produced by the United Kingdom [15], the United States [16][17][18][19] and Israel [20], though only the latter was a cohort study, and had some methodological limitations [21]. The greatest difficulty for individual-based mpox VE studies has been the lack of a sampling frame of the population targeted for vaccination, needed to identify vaccinated and unvaccinated groups that are similar in risk practices and risk of mpox virus (MPXV) infection, independently of the probability of receiving a dose of MVA-BN vaccine.…”
Section: Introductionmentioning
confidence: 99%